(untitled) (The Journal of Medicine, Humanity and Media, 2025)
Posters are crucial tools in public health for promoting health information and advocating healthy behaviors. In China, posters play a pivotal role in shaping public perceptions and attitudes towards COVID-19 vaccination by utilizing multimodal narratives. This paper emotionally with different demographic groups, including children, the elderly, and families. The findings indicate that by merging cultural values explores how poster designers synthesize textual and visual elements to resonate with text and images, the posters effectively foster an emotional appeal to different target audiences. This study provides valuable insights into the use of multimodal narratives in health communication and highlights the importance of culturally tailored messaging in public health campaigns.